Language ideologies, heritage language use, and identity construction among 1.5-generation Korean immigrants in New Zealand - Park, Mi Yung (International journal of bilingual education and bilingualism, 2022)
This article explores language ideologies, heritage language (HL) use, and identity construction among 1.5-generation Korean immigrants in New Zealand. Drawing on interview data, the study shows how language ideologies and identities influence these immigrants' language use and investment. All participants reported speaking Korean with their parents and adult members of their ethnic community, considering the use of English with these interlocutors to be inappropriate. The participants associated Korean language with their ethnocultural identities and viewed proficiency in their HL as essential in claiming Koreanness. The majority also reported 'mixing' Korean and English with siblings and friends, a practice they perceived as part of a shared 'Kowi' (Korean-Kiwi) identity. The participants' investment in HL use and maintenance was strongly tied to gaining cultural capital as Koreans in New Zealand; at the same time, they showed a lack of investment in further HL development. Constructing their identities as diasporic subjects, they did not regard native-like Korean fluency or advanced literacy skills as necessary or contributing to their socioeconomic capital. Based on the findings, this study offers implications for school administrators and policy makers in terms of how to support immigrants' HL development for the benefit of individuals, families, communities, and the nation.